Classification of lower body strength qualities: A data-driven approach - Geneau, M. C.; Gastin, P. B.; Robertson, S.; James, L. P. (International Journal of Sports Science & Coaching, 2025)
Maximal strength of the lower body is important for many athletic tasks and demands. Lower body extensor strength, defined as maximal expressions of force in the vertical plane, can be measured in several different ways, using a wide range of tests and metrics. Although there have been investigations into the interrelationships between lower body strength and force measures, there is no known analysis or synthesis of these data that focuses on classifying variables into groups based on statistical similarity and/or distinction. This information is important to consider in an environment where many measurement options exist for diagnosing lower body characteristics. Understanding the overlap and distinction of these analysis methods and metrics will inform parsimonious, yet comprehensive, assessment of the lower body. It was therefore the purpose of this review to explore and summarize the commonality (i.e., r, R2, component loading) between metrics from weightbearing, multi-joint lower body strength tests that are presented in the current literature, with the aim to group metrics into distinct domains of strength expression. The results of this review suggest that five unique domains of lower body extensor strength are present in athletes and trained populations: 1) reactive dynamic, 2) unloaded dynamic, 3) loaded dynamic, 4) early isometric, and 5) maximal isometric. Despite these findings, there are considerable limitations and gaps in the literature, and it is suggested that additional empirical investigations be conducted to better understand this concept of lower body strength domains.